Evaluation of Stevia leaf (Stevia rebaudiana Bertoni) powder as sugar-substitute in cashew nut fortified cookies - Dilrukshi, H.M.W.; Ulpathakumbura, B.S.K.; Gunarathna, K.M.R.U.; Iqbal, M.C.M.; Lai, O.M.; Marikkar, J.M.N. (University of Peradeniya, 2024)
Stevia rebaudiana is an herbal supplement used as a substitute for sugar in food processing. Considering the potentials of stevia as a zero-calorie-natural sweetener, this study aimed to assess the antioxidant and anti-hyperglycemic properties of stevia (Stevia rebaudiana Bertoni) leaf powder (SLP) to find its suitability to formulate low-calorie foods. Extracts of SLP obtained with hexane, ethyl acetate, and methanol were evaluated for DPPH, ABTS+, FRAP and enzyme inhibitory assays. Adopting a standard recipe, five different cookie types were prepared by incorporating varying proportions of SLP and evaluated by a 30 semi-trained panel. The nutritional composition and shelf-life stability were also evaluated. SLP had moisture (8.0 %), ash (13.5 %), crude protein (12.4 %), crude fat (6.9 %), crude fiber (18.3 %), and carbohydrate (40.9 %). Sensory results showed that the cookie formulated with the lowest amount of SLP (T1 = 2.0g) had the highest overall acceptability with the highest preference for appearance and smell. The cookie type formulated with the highest amount of SLP (T4 = 8.0g) had the highest crude protein (13.50%), crude fiber (21.76%), and lowest carbohydrate contents (40.88%). The keeping quality of the cookies remained acceptable within the storage period. These results suggest that acceptable quality cashew nut fortified cookies could be prepared by replacing sucrose with stevia leaf powder.